SOCIAL MEDIA MARKETING FACTORS AFFECTING CONSUMER PURCHASE INTENTION OF COSMETIC PRODUCTS IN JAKARTA, INDONESIA: THE MEDIATING ROLE OF CUSTOMER TRUST - Yunita Nidiah Indah, Permata; Choo, Dennis, Ying Hoe (INTI International University, 2023)
Today, customer depend on social media for product and service information which indirectly lead companies to optimise their spending on it. The research aimed to bridge the gap in the difficulty in quantifying the extent to which social media marketing could affect the purchase intention and impacts customers' purchasing decisions. The study examined impact of information quality on a brand’s social media content and electronic word of mouth on customer purchase intention; social media influencer impact on purchase intention of cosmetic product and trust as mediator of social media influencers and consumer purchase intention on the cosmetic product. Quantitative methodology was used to test the association between social media marketing factors (information quality, e-WOM, and social media influencers) toward purchase intention. 100 customers aged 18 to 50 from Jakarta, Indonesia completed online questionnaire through social media platforms (WhatsApp, Facebook, Instagram, and telegram). Smart PLS 4.0 software was used to analysed the data. The findings showed that social media information quality and electronic word of mouth positively affected customer purchasing intention; The effect of social media influencers’ negative direct effect on influenced customer intention. However, customer trust has a significant mediator effect between social media influencers and consumer purchase intention on the cosmetic product. The contribution of findings included better social media advertising; improve information quality; effective EWOM; need the right social media influencer to improve customer purchasing intention. The novelty of the research was that the study was conducted among Indonesian during post pandemic and the insignificant effect of social media influencers on customer purchase intention in Jakarta, which is contrary to several previous literatures.